Smartphone based alerting of first responders during the corona virus disease-19 pandemic: An observational study. Issue 27 (9th July 2021) - Ganter, Julian; Damjanovic, Domagoj; Trummer, Georg; Busch, Hans-Jörg; Baldas, Klemens; Hänsel, Mike; Müller, Michael Patrick
Abstract : Abstract: Smartphone alerting systems (SAS) for first responders potentially shorten the resuscitation-free interval of patients with acute cardiac arrest. During the corona virus disease-19 (COVID-19) pandemic, many systems are suspended due to potential risks for the responders. Objective of the study was to establish a concept for SAS during the COVID-19 pandemic and to evaluate whether a SAS can safely be operated in pandemic conditions. A SAS had been implemented in Freiburg (Germany) in 2018 alerting nearby registered first responders in case of emergencies with suspected cardiac arrest. Due to the pandemic, SAS was stopped in March 2020. A concept for a safe restart was elaborated with provision of a set with ventilation bag/mask, airway filter, and personal protective equipment (PPE) for every volunteer. A standard operating procedure was elaborated following the COVID-19 guidelines of the European Resuscitation Council. Willingness of the participants to respond alarms during the pandemic was investigated using an online survey. The response rates of first responders were monitored before and after deactivation, and during the second wave of the pandemic. The system was restarted in May 2020. The willingness to respond to alarms was lower during the pandemic without PPE. It remained lower than before the pandemic when the volunteers had been equipped with PPE, but the alarm response rate remained at approximately 50% during the second wave of the pandemic. When volunteers are equipped with PPE, the operation of a SAS does not need to be paused, and the willingness to respond remains high among first responders. Abstract : Supplemental Digital Content is available in the text